List of Members, By-laws, and Reports of the Wyoming Stock Growers Association, at 32, Important Resolutions no. 11 (1887) - (:unkn) unknown (My University, 1887)
That the custom of carrying firearms, except in the immediate vicinity of Indian reservations, should be discountenanced, and it is hereby made the duty of the members of this Association, foremen of round-ups, and foremen of ranges, to use every effort in their power to prevent the carrying of firearms by cattle men at all times and places except when absolutely necessary. Resolved, That the members of this Association hereby pledge themselves as far as in their power to carry out the spirit of this resolution."
Keywords: CARRY